"Do this in remembrance of me … ": A Lutheran defence of the sacrifice of the mass. (3rd July 2017) - Kringlebotten, Kjetil
Abstract : This essay discusses the sacrificial nature of the Eucharist within Lutheran theology, in dialogue with Roman Catholic theology. It starts by making some remarks on the controversial nature of the subject, the substance of the Roman Catholic doctrine of the "Eucharistic Sacrifice", and on Luther's removal of the Offertory, and his revision of the Eucharistic prayer or the Canon, before making some comments on the various views on the "Eucharistic Sacrifice" amongst the Church Fathers, the ecumenical and catholic aim of Confessio Augustana, and the Lutheran emphasis on God as giver and creation (including man) as receiver. After that, it returns to the main point, arguing for a "Eucharistic Sacrifice" within Lutheran theology, with emphasis on our participation in Christ, building on the contributions of Wolhart Pannenberg and Joseph Ratzinger, and against Lutheran critiques, here represented by John T. Pless.